Handlungsoptionen für die Rentenpolitik: Wie kann Alterssicherung nachhaltig(er) werden? - Gert G. Wagner (Wirtschaftsdienst, 2015)
– This article explores how German pension and retirement policy could be made more sustainable, focusing on selected current options for action rather than attempting to provide a comprehensive overview. Before turning to specific problems and perspectives, the article first discusses key challenges as well as opportunities for sustainable old age security in Germany and the European Union, and then applies these findings to attain a better understanding of acute problems.
Keywords: H11; H53; H55; I3; J14; 330; Rentenpolitik; Altersvorsorge; Nachhaltigkeit; Deutschland; EU-Staaten